Monitoring Walking Devices For Calorie Balance In Patients With Medical Rehabilitation Needs - Wahyu Andhyka Kusuma, WAK; Zamah Sari; Diah Ayu Fitriani; Siti Norhabibah; Sabrina Nurul Ubay; Hardianto Wibowo (Proceeding of the Electrical Engineering Computer Science and Informatics, 2018)
This article presents a measurement system intended to monitor human footsteps. The goal is to guide the users medical rehabilitation incorrect use to prevent dangerous situations and maximize comfort. Indicators of risk in question: the imbalance of movement in motor coordination and the number of calories to be burned for medical rehabilitation patients by balancing the patient's needs. Measurements are made by placing the sensor on one of the patient's legs. The main sensor accelerometer used in this study. The measurement system comes with an application link that allows patients and therapists to monitor the activity. Calibration and experimental results are presented in this article.